Dismantling The Effective Strategy of PGMI INSIP Learning Media In Increasing Interest In Learning Social Sciences - Ridwan ridwan; Niken Rahmawati (Yayasan Azhar Amanaa Yogyakarta, 2026)
Interest in learning is one of the determining factors for students' success in understanding Social Sciences courses in the PGMI Study Program. The purpose of the research is to analyse the condition of PGMI INSIP students' learning interests in Social Sciences courses. And identify the types of learning media that lecturers have been using in lectures. This study uses a qualitative approach with a descriptive case study. The sample consisted of 3 lecturers teaching Social Sciences courses, 12 PGMI students in semesters 2, 4, and 6, 1 Head of PGMI Study Program, and 1 Administrative Staff. The main instrument in qualitative research is the researcher himself (human instrument). To support data collection, auxiliary instruments were used in the form of Observation Guidelines, Semi-Structured Interview Guidelines, Documentation, and Field Notes. It is used by researchers to record important phenomena during the study. Data analysis uses the Miles, Huberman, and Saldana models, through the stages of Data Reduction, Data Presentation (Data Display), and Conclusion Drawn. The results of the study show that the effective strategy of learning media at PGMI INSIP lies in the use of interactive, visual, collaborative, and digital technology-based media such as Canva, Quizizz, learning videos, and digital social case studies. This study found that PGMI INSIP students are more interested in learning that combines visual elements, group discussions, gamification, and the relationship of the material with social realities in society. This research contributes in the form of a conceptual model of learning media strategies for the PGMI Study Program in increasing students' interest in learning in Social Sciences courses.